Regionalism, end markets and ownership matter: Shifting dynamics in the apparel export industry in Sub Saharan Africa - Mike Morris; Cornelia Staritz; Leonhard Plank (Austrian Foundation for Development Research (ÖFSE), 2014)
This paper shows the importance of ownership, end markets and regionalism within the global value chain (GVC) conceptual framework. This is done through unpacking the development trajectories of the major Sub Saharan African (SSA) apparel export industries (Mauritius, Madagascar, Kenya, Lesotho, Swaziland) against the backdrop of global and regional trade regime changes and the manner in which different supplier firms react to these opportunities and/or constraints. These trajectories demonstrate the emergence of a new regionalism centred around investment and differentiated end markets. Ownership characteristics of supplier firms shape the ability to shift between different end markets and respond to lead firm requirements; and the level of their local and regional embeddedness impacts on different forms of upgrading. More locally and regionally embedded firms in these SSA countries have been able to shift with uneven success to new, and in particular regional, markets. In contrast, Asian-owned transnational producers remain focused on the US market with limited market opportunities and upgrading potential. Different types of ownership and embeddedness dynamics are therefore important to explain the co-evolution of highly differentiated value chain dynamics creating a variety of apparel industrialization trajectories in the apparel export industry in SSA.
Keywords: 330; global value chains; apparel; upgrading; ownership; Sub Saharan Africa; global value chains; apparel; upgrading; ownership; Sub Saharan Africa